Sistem Pendukung Keputusan Untuk Menentukan Lokasi Usaha Kuliner Yang Strategis Menggunakan Metode Naive Bayes - Muiza Ulin Nuhayati; Dedih Dedih; Jajang Mulyana (Jurnal Interkom: Jurnal Publikasi Ilmiah Bidang Teknologi Informasi dan Komunikasi, 2017)
Decision Support System is a software developed specifically to assist in the decision making process. Decision support system for determining the location of strategic culinary business is treated as a "second opinion" or "information sources" that can be used as a material consideration before deciding to take a decision when going to open a business in the selected location. The design of this system using the programming language PHP, Apache as the Web server and MySQL as DBMS (Database Management System). pengebangan this system using SDLC Waterfall. This meth od used in the decision support system is using Naive Bayes method that predicts the chance that will happen in the future based on past events. so that in addition to attracting users, this system is expected to represent the real-world situation or the actual business.